Effectiveness model of nursing care for the family of patients with acute myocardial infarction in intensive care unit - Garcia Avendaño, David Jahel; Estrada Ochoa, Ma. Cristina; Gallegos Alvarado, Mónica; Antuna Canales, Ana Beatriz (Revista Cuidarte, 2015)
ntroduction: This research protocol is intended to interfere with the family and to determine the effectiveness of the model of nursing care for the family of patient with acute infarction myocardium (AMI) in the intensive care unit (ICU). Materials and Methods: Descriptive study of family intervention Results and Discussion: 100% Of families responded affirmatively to the family nurse them informed about the care the family according to needs identified, established a plan of action in family same which met and it is interested for that as far as possible agreeable stay in the family. Conclusions: The results of this investigation of intervention with AMI in the ICU patient families brings results that support the importance of implementing a care model of nursing family in these units.